Legal Justice in Aceh’s Gala Agreement for Local Economic Empowerment - Sulaiman Sulaiman; Muhammad Nasir; Yusrizal Hasbi; Jumadiah Jumadiah (Magister of Law, Faculty of Law, University of Mataram, 2026)
The gala concept is a traditional agreement practiced by the Acehnese community to support economic empowerment based on local wisdom. Despite its continued use, limited research has examined the gala agreement in relation to Aceh’s special autonomy under Act No. 11 of 2006 concerning the Government of Aceh and its compatibility with Islamic economic principles. This study aims to analyze the form and implementation of the gala agreement within the framework of Islamic economics as a socio-economic practice that continues to operate in Acehnese society. This research adopts a socio-legal approach by drawing on both primary and secondary data. The analysis is carried out normatively to evaluate the consistency of gala practices with the principles of contract law, and sociologically to examine the evolving notions of justice within society. The results indicate that the implementation of economic empowerment through the gala model reflects the philosophical principles of Islamic economics, particularly mutual assistance (ta‘āwun) and social solidarity. However, in practice, the gala system still contains elements resembling interest due to the use of collateral and certain benefit arrangements by the gala provider, which creates inconsistencies with Shariah economic principles. Nevertheless, gala practices embody important social values such as justice, welfare, equality, trust, and religiosity within Acehnese society, while community leaders play a crucial role in maintaining their legitimacy. The novelty of this study lies in its reinterpretation of the gala agreement as a community-based financial model that integrates local wisdom, Islamic economic values, and Aceh’s special autonomy framework, while proposing its conceptual development toward a more structured and Shariah-compliant contract system.